Sunteți pe pagina 1din 49

A

x

A k ∈ {1, 2,

f a

R n (x 1 ,

f

,x

n )

A

a

=

:

A R

n )

=

(a 1 ,

,n}

,a

x k

lim

x k a k

f(a 1 ,

,a

k1 , x k , a k+1 ,

,a

n ) f(a 1 ,

,a

n

)

x k a k

f x k a f x k (a)

B A f x k (x) x B

f : A R 2 R (x 0 , y 0 )

∂f

k (a)

n

∂x x k 1 k

f

∂f

∂x

(x 0 , y 0 ) =

f x (x 0 , y 0 ) =

lim

xx 0

f (x, y 0 ) f(x 0 , y 0 )

x x 0

∂f

∂y

(x 0 , y 0 ) = f y (x 0 , y 0 ) =

lim

yy 0

f(x 0 , y) f(x 0 , y 0 )

y y 0

.

2 f

=

∂x k ∂x i

∂x k ∂x i

f

x

2

i

f

x

k x i = (f

x k ) x i

 1 ≤ i, k ≤ n i = k ∂ 2 f ∂ 2 f = 2

∂x

i

∂x i ∂x i α = (α 1 ,

= f i x i

x

p ) N p

|α| |α| = α 1 + α 2 + ··· + α p

|α|

f

x

α 1

1

x

α

p

p

|α| f

∂x α 1

1

∂x

α

p

p

.

f : A R n R

f

a intA

a f

x i x k

f

V

x

k x i

k x i (a) = f i x k (a)

x

x

D R m A

R n u = (u 1 ,

u 1 ,

D f C 1 (A) F : D R

n x k 1 k m

A

,u n )

:

D

,u

F(x) = f(u 1 (x),

,u

n (x))

x k D

∂F

∂x k

=

∂f

∂u 1

· ∂u 1 ∂x

k

+

∂f

∂u 2

· ∂u 2 ∂x

k

+ ··· +

∂f

∂u m

· ∂u m ∂x k

.

A R n f : A R f : A R n

f = (f ) =

∂f

∂x 1

,

∂f

∂x 2

,

,

∂f

n

∂x

f f

f F = (f 1 , f 2 ,

f i F : A R

,f n ) : A R n

F = ∂x f 1

1

+

∂f 2

∂x 2

+ ··· +

∂f n

∂x n

F

f : A R Δf : A R

Δf = 2 f + 2 f + ··· +

∂x 2

1

∂x 2

2

2 f

∂x

2

n

f f

Δf = (f ) = ∇ · (f ).

= (f 1 , f 2 , f 3 ) :

F A R 3 R 3

∂f 3 ∂x 1

=

∂f 3

∂x 2

∂f 2 ∂x 3

,

∂f

1

∂x

3

F

,

∂f 2

∂x 1

∂f 1 ∂x

2 .

F =

i

∂x 1

f 1

j

∂x 2

f 2

k

∂x 3

f 3

not

= ∇ × F.

m ) : A R m

f i

A

R n a

E F

=

(f 1 , f 2 ,

,f

J F (a) =

∂f

1

∂x

∂f 2

1

∂x

1

∂f m

∂x 1

(a)

(a)

(a)

∂f

1

∂x

∂f 2

2

∂x

2

(a)

(a)

f ∂x m 2 (a)

∂f 1

∂x

∂f 2

n

∂x n

f m

∂x n

(a)

(a)

(a)

F a m = n F a

A R n

J F (a) = D(x D(f 1 1 , ,

,f n )

) (a).

,x

n

a intA s R n

s = 1

f

: A R

s a

lim

t0

f (a + ts) f (a)

t

f s a

ds df (a)

f : A R A R n a intA

s = (s 1 ,

,s n ) R n s = 1

ds df (a) = f x 1 (a)s 1 + f x 2 (a)s 2 + ··· + f x n (a)s n = f (a) · s.

f

:

I

R

I

R a intI f(x) f(a)

f (a) = lim

xa

x a

lim

xa

f(x) f(a) f (a)(x a)

x a

lim

xa

f(x) f(a) T(x a)

x a

=

0,

= 0

T T : R R T (h) =

f (a)h f (x)f (a) = T (xa) a f a T T f a df (a) f a a

T (h) = df (a)(h) = f (a)h

1 R : R R 1 R (x) = x x R d1 R (x)(h) = h h = dx

 df (x)(dx) = f (x)dx f : A → R A ⊆ R n a ∈ intA f a ∈ intA T : R n → R

lim

xa

f(x) f(a) T(x a)

x a

= 0.

(3)

T f a df(a)

R A R n a intA

df (a) : R n R

∂f

f

:

A

df (a)(h) = ∂x f 1 (a)h 1 +

,h

∂f

∂x n

∂f

∂x n

x 2 (a)h 2 + ··· +

(a)h n ,

h = (h 1 , h 2 ,

n ) R n

h k = dx k 1 k n h = dx

df (a)(h) = ∂x f 1 (a)dx 1 +

∂f

2 (a)dx 2 + ··· +

(a)dx n .

∂x

A R n f C 1 (A) f A

f,g : A R a intA

d(f + g)(a) = df (a) + dg(a)

d(λf )(a) = λdf (a),

λ R

d(fg)(a) = f (a)dg(a) + g(a)df (a)

d f

g

(a) = g(a)df (a) f (a)dg(a) g 2 (a)

,

g(a)

= 0.

R A R n B

a intA f (a) intB gf : A R a

f

: A B g : B

R

d(g f )(a) = dg(f (a)) df (a).

n f

f

C p (A)

A

R m

=

d n f(x) =

∂x 1

n!

∂x

m

dx m n f(x)

(x)dx k 1

1

dx 1 + ··· +

m ! ∂x k 1

1

k 1 +···+k m f

∂x

k

m

m

k 1 !k 2 !

k

k 1 +···+k m =n

n = 2

=

dx

k

m

m .

d 2 f(x) =

n

k=1

2 f(x)

∂x 2

k

dx k

2 + 2

1j<kn

2 f(x)

∂x k ∂x j

dx k dx j .

A R n

f C m+1 (A) a A [a, x]

x A ξ

f(x) = f(a) + df (a)(x 1! a)

+ ··· + d m f (a)(x a) m!

d m+1 f (ξ)(x a)

(m + 1)!

+

.

f : D R m D R n ×R m f = (f 1 ,

A R n B R m A × B D g : A B f (x, g(x)) = 0 x A f (x, y)=0 f (x, y)=0 y x

m )

,f

D R n × R m

f : D R m f = (f 1 ,

,f m ) (x 0 , y 0 ) D

f (x 0 , y 0 )=0

f

C 1 (D, R m )

D(f 1 , D(y 1 ,

,f

m

)

,y

m

)

(x 0 , y 0 )

= 0

U x 0 R n V

R m U × V

D g : U

V

y 0

g(x 0 ) = y 0 f (x, g(x)) = 0 x U g U

D R 2

D R 2 (x 0 , y 0 ) D R

f (x 0 , y 0 )=0

f

f y (x 0 ,

= 0

C 1 (D, R)

y 0 )

f : D

U x 0 V y 0 U×V D

g : U V

g(x 0 ) = y 0

f (x, g(x)) = 0 x U

g U g (x) = f

x (x, g(x))

f y (x, g(x))

x U

f (x, y)=0

x y

f x (x, y) + f y (x, y) · y = 0,

f C k g k f (x, y)=0

x

y

= g(x)

a D

f V a

f

:

D

R D R n

f (a) f (x)

(f (a) f (x)),

x V D.

a D f f (a) f (x) f (a) f (x) x D f

a intD f f a f (a)=0

a D f (a)=0 f a D

f x 1 (a)=0, f x 2 (a)=0,

,

f x n (a)=0.

D R n f f

C 2 (D) a D

2 f (a) a f 2 f (a) a f 2 f (a) a f

D R 2 f C 2 (D) (x 0 , y 0 ) f

2 f(x 0 , y 0 ) = p x 2 + 2q x y + y 2 ,

p = f

δ > 0 (x 0 , y 0 ) f δ < 0 p > 0 (x 0 , y 0 ) f

δ := q 2 pr

x

2 (x 0 , y 0 ) q = f xy (x 0 , y 0 ) r = f

y

2 (x 0 , y 0 )

δ < 0 p < 0 (x 0 , y 0 ) f

ϕ : R n R A λ 1 , λ 2 ,

A Δ 1 , Δ 2 ,

n

,

Δ n

ϕ λ 1 > 0, λ 2 > 0,

Δ 1 > 0, Δ 2 > 0,

n > 0

n < 0

Δ n > 0

, ϕ λ 1 < 0, λ 2 < 0,

, ϕ A

Δ 1 < 0, Δ 2 > 0, Δ 3 < 0,

(1) n Δ n > 0

D R n f m m<n

C

= {x D | g 1 (x)=0,

,g

: D R

g 1 , g 2 ,

m (x)=0}, x = (x 1 ,

,g

m : D R

,x

n ).

a C

a f | C f C

g 1 (x)=0, g 2 (x)=0,

,

g m (x)=0

G = (g 1 ,

,g

n ) : D R m

L : D × R m R

L(x, λ) = f (x) + λ 1 g 1 (x) + ··· + λ m g m (x),

λ

= (λ 1 ,

m ) R m .

D f,g 1 ,

C 1 (D)

J G (a) = m λ 0 = (λ 0 , λ 0 2 ,

m

a C f

,g

0

m ) R m

1

L x k (a, λ 0 )=0, 1 k n

g j (a)=0,

1 j m

L f λ 0 , λ 0 2 ,

1

0

m

a (a, λ 0 ) L

D f,g 1 ,

C 1 (D) (a, λ 0 ) C × R m L

h R n \ {0} G(a)(h)=0

,g

m

2 L(a, λ 0 )(h) > 0

( 2 L(a, λ 0 )(h) < 0),

a f

A R n B R F C 2

F (x, y)=0

: A × B

R

y = g(x) (x 0 , y 0 ) A × B

F x 1 (x, y)=0 F x 2 (x, y)=0

F x n (x, y)=0 F (x, y)=0

2 y

F F (x) = f (u(x), v(x)) f : R 2 R C 2 u, v : (0, +) R u(x) = x 2 + 1 v(x) = ln x F F (x, y) = f (u(x, y)) f : R R C 2 u(x, y) = xy F

F (x, y) = f (u(x, y), v(x, y)) f : R 2 R

C 2 u(x, y) = xy v(x, y) =

x

x

y

= 0

F (x) = f u (u(x), v(x)) · 2x + f v (u(x), v(x)) · 1

x f u (u(x), v(x)) f v (u(x), v(x))

F (x) = f 2 · 2x + f

u

uv ·

x · 2x + f u · 2+

1

+ f uv · 2x + f v 2 ·

1

x

· x + f v · 1 2 =

1

x

=

4x 2 f 2 +

u

1

2 f

x

v

2 + 4f uv + 2f u

1 2 f v .

x

F x (x, y) = f (u(x, y)) · u x (x, y) = f · x

F y (x, y) = f ·

1 + x 2 y 2

2 (x,

F

x

y)

=

f

·

y 2 (1 + x

2 y 2 ) 2

y

1 + x 2 y 2

+

f

·

2xy 3 (1 + x 2 y 2 ) 2

2 (x,

F

y

F xy (x,

y)

=

f

·

y) = f ·

x 2 (1 + x

xy (1 + x

2 y 2 ) 2

2 y 2 ) 2

+

+

f

·

f ·

2x 3 y (1 + x 2 y 2 ) 2

1 x 2 y 2 (1 + x 2 y 2 ) 2

F x (x, y) = f u · y + f

v y 2 F y (x, y) = f u · x + f v ·

x

1

x

,

,

.

F 2 (x, y) = f 2 · y + f uv (

x

u

2 ) · y+

y

x

+ f uv · y + f 2 · (

v

2 ) · (

y

x

y

v · 2y x 3 ,

2 ) + f

x

F 2 (x, y) = f 2 · x + f

y

u

uv · 1

x · x + f uv · x + f

v

2

·

F xy (x, y) = f 2 · y +

u